1988
DOI: 10.1037/0012-1649.24.4.532
|View full text |Cite
|
Sign up to set email alerts
|

Young children's conception of distance.

Abstract: Whether young children conceive of distance as rigid intervals of extent seems central to their larger understanding of space and to their measurement abilities (Piaget, Inhelder, & Szeminska, 1960). A sensitive test of children's conception of distance would require them to reason about distance rather than simply visually to estimate displayed lengths. Therefore, we investigated preschoolers' understanding of two distance principles. The direct-indirect principle is the idea that a straight route between two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Given that this original LT was based on a review of research available at that time , such findings replicate the previous research and provide additional empirical support for the LT described in Table 1. For example, they indicate that development of length concepts and skills is a slow and extended process, but that young children do have the ability to understand and learn these ideas (Bartsch & Wellman, 1988;Ellis et al, 2003;Hiebert, 1981;Miller & Baillargeon, 1990;Nunes & Bryant, 1996). They reliably move through the levels posited; for example, most pass into and through the End-to-End Length Measurer level, in which they place multiple units or begin to iterate a unit but leave gaps between units (Lehrer, 2003).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Given that this original LT was based on a review of research available at that time , such findings replicate the previous research and provide additional empirical support for the LT described in Table 1. For example, they indicate that development of length concepts and skills is a slow and extended process, but that young children do have the ability to understand and learn these ideas (Bartsch & Wellman, 1988;Ellis et al, 2003;Hiebert, 1981;Miller & Baillargeon, 1990;Nunes & Bryant, 1996). They reliably move through the levels posited; for example, most pass into and through the End-to-End Length Measurer level, in which they place multiple units or begin to iterate a unit but leave gaps between units (Lehrer, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…They posited that young children did not possess understanding of length, based on interviews in which children appeared to believe that placing an object between two positions changed the distance between these positions (Miller & Baillargeon, 1990). However, children 3.5-5 years of age appear to understand these concepts in some settings (Bartsch & Wellman, 1988). Similarly, the Piagetians argued that meaningful measurement and indirect comparison using transitive reasoning is impossible until children conserve length.…”
Section: Original Length Learning Trajectorymentioning
confidence: 98%
“…Previous studies (e.g., Bartsch & Wellman, 1988;Fabricius & Wellman, 1993;Miller & Baillargeon, 1990) suggested that measurement abilities may emerge by this age. If the effect we observed in 2-year-olds is due to inability to impose a measure, 4-year-olds might be able to discriminate extent even for an isolated dowel.…”
Section: Experiments 4: Discrimination In 4-year-oldsmentioning
confidence: 97%
“…It is seen that other performed researches on children's competence (Zimmerman & Whitehurst, 1979;Zimmerman & Blom, 1983a, 1983bStiles-Davis, 1988;Bartsch & Wellman, 1988;Sophian, 1988;English, 1993;Fabricius & Wellman, 1993) did not support Piaget. For example, according to the results that Rosenthal and Zimmerman (1978) found in their researches, it was seen that children in the pre-operational stage successfully completed the cognitive features of the concrete operational stage after the training including oral expression and modeling.…”
Section: Critiques Directed To Piaget On Language and Concept Developmentioning
confidence: 99%